(untitled) (Journal of Comparative & International Higher Education, 2024)
Despite ample literature regarding acculturative stress among international students, there is a gap in the literature synthesizing the sources of acculturative stress and the coping strategies that can help international students to deal with acculturative stress. In this systematic literature review, we aim to investigate the current state of acculturative stress among international students, through empirical research published in peer-reviewed journals between the years 2018 and 2022. Using a predetermined review protocol, this review analyzed 66 publications on acculturative stress for international students. These studies were mainly published in 2021 in the Journal of International Students. The preliminary findings provide a comprehensive range of sources for acculturative stress that can be broken down into four levels: Macro (socio-economic factors from both home and host countries or national level), Meso (institutional factors), Micro (individual, personal, or psychosocial factors). Drawn upon the sources of acculturative stress, international students are expected to reduce acculturative stress by improving their English proficiency, practicing self-compassion, adopting a positive perspective, adjusting expectations and perfectionism, attending serious leisure engagement, and seeking social support. The findings from this review will be used to help policy makers and university leaders and managers to better optimize their resources to improve international students’ acculturation experience and enhance the overall higher education system.